Microwave-Assisted Synthesis of Azines and their Condensed Derivatives - Elgemeie, Galal; Abd Elaziz, Hanaa (Current Microwave Chemistry, 2015)
In recent years, numerous reports concerning the synthesis of azines and their fused derivatives under microwave irradiation condition have appeared. The use of microwave heating is a valuable tool for synthetic chemists. Being able to reduce reaction times and to increase product yield, this methodology offers to organic chemists the potential to optimize reaction processes. Additionally, application of microwave irradiation leads to many advantages, like the use of non-corrosive and inexpensive reagents, in addition to the eco-friendly and quot; green chemistry and quot; economical and environmental impacts. In this review, we report the important role of microwave activation and their advantages in the synthesis of medically important azines and their fused derivatives.
Keywords: hantzsch synthesis